Fixing member and thermal fixing device
Patent Information
- Application Number
- JP2021093094
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-02
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2041-06-02
AI Technical Summary
【0010】 本開示の一態様によれば、定着工程において通紙領域における厚み方向の熱伝導性が高く、非通紙領域においては過度の昇温を防止し得る定着部材を得ることができる。また、本開示の他の態様によれば、高品位な電子写真画像を安定して形成し得る熱定着装置の提供に向けたものである。本開示の一態様によれば、通紙領域での厚み方向への高い熱伝導性、ならびに、繰り返し圧縮などに対する高耐久性を有し、さらには非通紙領域の過度の昇温を抑制するために有効な熱定着装置用の定着部材が提供される。
Smart Images

Figure 0007631107000007 
Figure 0007631107000008 
Figure 0007631107000009
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a fixing member used in a thermal fixing device of an electrophotographic image forming apparatus such as a copier, a printer, etc. The present disclosure also relates to a thermal fixing device using the fixing member. [Background technology]
[0002] In a thermal fixing device used in an electrophotographic system such as a copying machine or a laser printer, a pair of rotatable members, such as a pair of heated rollers, a film and a roller, a belt and a roller, or a belt and a belt, are pressed together. A recording medium carrying an image formed with unfixed toner (hereinafter also referred to as an "unfixed toner image") is introduced into the pressure contact area (hereinafter also referred to as the "fixing nip") formed between these members, and the unfixed toner is heated and melted to be fixed to the recording medium.
[0003] A rotatable member for heating in a thermal fixing device with which an unfixed toner image held on a recording medium comes into contact is called a fixing member, and is called a fixing roller, fixing film, fixing belt, or the like depending on its shape.
[0004] In recent years, the output of a uniform gloss image has been required even for chromatic images. To form a uniform gloss image, it is effective to make the surface of the fixing member follow the uneven shape of the paper in the fixing nip and apply heat and pressure uniformly to the unfixed toner image. For this reason, some fixing members have an elastic layer containing rubber such as silicone rubber. In fixing members equipped with such an elastic layer, further improvement in the thermal conductivity in the thickness direction of the elastic layer is required from the viewpoint of further improving the print speed and improving energy saving. However, if a large amount of thermally conductive filler is contained in the elastic layer to provide high thermal conductivity, the hardness of the elastic layer may increase and the elastic function may be impaired. Therefore, it is necessary to devise a way to increase the thermal conductivity without increasing the amount of thermally conductive filler. Patent Document 1 discloses a method of obtaining a fixing member having high thermal conductivity in the thickness direction and low hardness by orienting the filler in the thickness direction by the action of an electric field. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2019-215531 A Summary of the Invention [Problem to be solved by the invention]
[0006] According to the study by the present inventors, in the fixing member according to Patent Document 1, it was possible to improve the thermal conductivity in the thickness direction of the elastic layer while suppressing the filler content in the elastic layer. However, there were cases where the thermal conductivity in the in-plane direction of the elastic layer of the fixing member according to Patent Document 1 was relatively decreased. In such a fixing belt, the temperature of the area not in contact with the paper (hereinafter also referred to as the "non-paper passing area") may become high in the process of thermally fixing unfixed toner to paper.
[0007] One aspect of the present disclosure is to provide a fixing member that has high thermal conductivity in the thickness direction in an area that contacts paper during a fixing process (hereinafter, also referred to as a "paper passing area") and can prevent excessive temperature rise in a non-paper passing area. Another aspect of the present disclosure is to provide a thermal fixing device that can stably form high-quality electrophotographic images. [Means for solving the problem]
[0008] According to one aspect of the present disclosure, there is provided a method for manufacturing a pressure-sensitive adhesive sheet comprising: the elastic layer includes a silicone rubber and a filler dispersed in the silicone rubber, When the thermal conductivity of the elastic layer in the thickness direction is λnd, the thermal conductivity in the longitudinal direction is λmd, and the total length of the elastic layer in the longitudinal direction is L, The λnd / λmd in a central region of the elastic layer that is 0.12×L or more from each end of the elastic layer in the longitudinal direction toward the center of the elastic layer in the longitudinal direction is 1.1 or more, and The elastic layer has end regions in which λnd / λmd is 0.9 or less between each longitudinal end of the elastic layer and 0.12×L toward the longitudinal center of the elastic layer, and a fixing member for a thermal fixing device is provided.
[0009] According to another aspect of the present disclosure, there is provided a thermal fixing device having a fixing member for heating and a pressure member arranged opposite the fixing member, the fixing member being the fixing member described above. Effect of the Invention
[0010] According to one aspect of the present disclosure, a fixing member can be obtained that has high thermal conductivity in the thickness direction in the paper passing area during the fixing process and can prevent excessive temperature rise in the non-paper passing area. In addition, according to another aspect of the present disclosure, the present disclosure is directed to providing a thermal fixing device that can stably form high-quality electrophotographic images. According to one aspect of the present disclosure, a fixing member for a thermal fixing device is provided that has high thermal conductivity in the thickness direction in the paper passing area, high durability against repeated compression, etc., and is also effective in suppressing excessive temperature rise in the non-paper passing area. [Brief description of the drawings]
[0011] [Figure 1] 3A and 3B are conceptual diagrams illustrating the direction of heat conduction of a fixing member according to an embodiment of the present disclosure, where (a) is a perspective view and (b) is a schematic cross-sectional view taken along line AA of (a). [Diagram 2] 1A and 1B are conceptual diagrams for explaining the thermal conductivity of each longitudinal region of an elastic layer in a fixing member of an embodiment of the present disclosure, in which (a) shows positions 0.05L and 0.12L from both ends, (b) is a schematic diagram showing a first form of the elastic layer of a fixing member having no intermediate region, and (c) is a schematic diagram showing a second form of the elastic layer of a fixing member having an intermediate region. [Diagram 3] FIG. 2 is a conceptual diagram for explaining the orientation and arrangement state of a filler in an elastic layer of the present disclosure. [Figure 4] 2A and 2B are an overhead view and a cross-sectional view, respectively, of a corona charger for forming an elastic layer of a fixing member according to an embodiment of the present disclosure. [Diagram 5] 1A and 1B are schematic cross-sectional views of fixing members according to embodiments of the present disclosure, in which (a) is in belt form and (b) is in roller form. [Figure 6] 3A and 3B are diagrams illustrating a first cross section and a second cross section of an elastic layer of a belt-shaped fixing member. [Figure 7] 4 is a schematic diagram showing a method for confirming the degree and angle of alignment of a filler in an elastic layer. FIG. [Figure 8] FIG. 2 is a schematic diagram showing an example of a step of laminating a surface layer. [Figure 9] FIG. 2 is a schematic cross-sectional view of an example of a thermal fixing device using a fixing belt and a pressure belt. [Figure 10] FIG. 2 is a schematic cross-sectional view of an example of a thermal fixing device using a fixing belt and a pressure roller. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, embodiments of the present disclosure will be described in detail. FIG. 1 is a conceptual diagram for explaining the direction of heat conduction of a fixing member (hereinafter also referred to as a “fixing belt”) 100 having an endless shape according to one embodiment of the present disclosure, in which (a) is an oblique view and (b) is a diagram showing a cross section taken along line AA in (a), i.e., a cross section in a direction perpendicular to the circumferential direction. The fixing belt 100 has an elastic layer 4 on the peripheral surface of a substrate 3 having an endless shape. Here, the thermal conductivity of the elastic layer 4 in the thickness direction (nd) is λnd, and the thermal conductivity of the elastic layer 4 in the longitudinal direction (md) is λmd. As shown in FIG. 1(a), the fixing belt 100 is rotatable, and the direction of rotation is called the circumferential direction (rd) of the fixing belt. The longitudinal direction (md) of the elastic layer is defined as the direction perpendicular to the circumferential direction of the fixing belt. In the fixing belt 100, the ratio of thermal conductivity in the thickness direction to the longitudinal direction of the elastic layer (λnd / λmd, also called thermal anisotropy) is controlled in the longitudinal region, thereby achieving efficient heat supply to unfixed toner and suppressing excessive temperature rise in non-paper passing regions. Specifically, the elastic layer 4 of the fixing belt 100 contains silicone rubber and a filler dispersed in the silicone rubber. Here, the thermal conductivity of the elastic layer in the thickness direction is λnd, the thermal conductivity of the elastic layer in the longitudinal direction is λmd, and the total length of the elastic layer in the longitudinal direction is L. In this case, the elastic layer has a λnd / λmd of 1.1 or more in a central region that is 0.12×L or more from each longitudinal end of the elastic layer toward the longitudinal center of the elastic layer. The elastic layer also has end regions where λnd / λmd is 0.9 or less between each longitudinal end of the elastic layer and 0.12×L toward the longitudinal center of the elastic layer.
[0013] FIG. 2 is an explanatory diagram of thermal anisotropy for each region in the longitudinal direction of the elastic layer 4 of the fixing belt 100 according to one embodiment of the present disclosure. As shown in FIG. 2(a), when the total length of the elastic layer 4 in the longitudinal direction is L, as shown in FIG. 2(b), the central region 4c having a length of 0.12×L or more from each end of the elastic layer in the longitudinal direction toward the center of the elastic layer in the longitudinal direction corresponds to a region with which paper frequently comes into contact in the fixing process (hereinafter, also referred to as a "paper passing region"). Here, "0.12L or more" is a value based on, for example, a paper width of 297 mm (51.5 mm on both sides of the non-paper passing width, 51.5 / 400≒0.12) when the total length L of the fixing member in the longitudinal direction is 400 mm. The thermal conductivity ratio λnd / λmd in this region is 1.1 or more. In addition, as shown in FIG. 2(c), the elastic layer of the fixing belt according to one embodiment of the present disclosure has end regions 4a in which λnd / λmd is 0.9 or less in a region from each end of the elastic layer in the longitudinal direction to 0.12×L toward the center of the elastic layer in the longitudinal direction. The region from both ends of the elastic layer in the longitudinal direction to 0.12×L toward the center of the elastic layer in the longitudinal direction corresponds to a non-paper passing region where paper may not come into contact in the fixing process. Among them, the region from the end of the elastic layer in the longitudinal direction to 0.05×L toward the center of the longitudinal direction is a region that is particularly likely not to come into contact with paper in the fixing process. Here, "0.05×L" is a value based on a paper size width of 297 mm (non-paper passing width on both sides 16.5 mm, 16.5 / 330≒0.05) when the total length L of the fixing member in the longitudinal direction is, for example, 330 mm. Therefore, in the fixing belt according to the present disclosure, the region from both ends of the elastic layer in the longitudinal direction to 0.05×L toward the center of the elastic layer in the longitudinal direction is preferably the end region. In the fixing belt according to the present embodiment, the central region 4c is located at a position 0.10×L or more from both ends of the elastic layer in the longitudinal direction. In addition, the end region 4a includes a region of 0.05×L from both ends of the elastic layer in the longitudinal direction toward the center, and is adjacent to the central region 4c. In the central region 4c, λnd is higher than λmd, and λnd / λmd is 1.1 or more, so that efficient heat conduction in the thickness direction is achieved. As a result, unfixed toner can be fixed more efficiently in the fixing process. In the central region 4c, λnd is more preferably 1.3 W / (m·K) or more in terms of fixability. In the edge region 4a, λmd is higher than λnd, and λnd / λmd is 0.9 or less, so that the temperature rise in the non-paper passing region where the recording medium does not pass can be suppressed. Here, it is more preferable that λmd in the edge region 4a is 1.3 W / (m·K) or more in terms of suppressing the temperature rise in the non-paper passing region.
[0014] As a method for increasing the thermal conductivity in the thickness direction without increasing the amount of thermally conductive filler blended in the elastic layer, there is a technique for arranging fillers by an external field such as a force field, a magnetic field, or an electric field. Inorganic oxides such as alumina, silica, zinc oxide, and magnesium oxide are generally used as thermally conductive fillers blended in the elastic layer of the fixing member, and they have a high affinity for alignment by an electric field using dielectric polarization as a driving force. The present inventors have highly aligned small particle size fillers between large particle size fillers in the paper passing region of the elastic layer while suppressing the alignment of large particle size fillers in the thickness direction (nd) by using the filler alignment technique using an electric field according to Patent Document 1. As a result, a thermal conduction path is formed by a group of small particle size fillers between the large particle size fillers, and the thermal conductivity in the thickness direction can be increased. Since there is no need to increase the amount of filler, it is possible to achieve even higher thermal conductivity while suppressing an increase in hardness.
[0015] Furthermore, in this disclosure, the elastic layer is divided into regions in the longitudinal direction, and an electric field is applied to control the orientation, thereby increasing the thermal conductivity in the thickness direction in the central region, which is the paper passing region of the recording medium, and increasing the thermal conductivity in the longitudinal direction on both ends, which correspond to the non-paper passing regions. As a result, it has been found that it is possible to suppress the temperature rise in the non-paper passing regions while achieving high fixability for unfixed toner.
[0016] FIG. 2(c) is an explanatory diagram of thermal anisotropy for each region of the elastic layer of the fixing belt according to another embodiment of the present disclosure. In the elastic layer according to this embodiment, the end region 4a is present in an area of 0.05×L from both ends of the elastic layer in the longitudinal direction toward the center, and the central region 4c is present at a position of 0.10×L or more from both ends of the elastic layer in the longitudinal direction. The intermediate region 4b is provided between the end region 4a and the central region 4c. The intermediate region 4b has a λnd / λmd of more than 0.9 and less than 1.1. That is, the intermediate region 4b functions as a transition region from the central region 4c to the end region 4a with respect to the thermal conductivity in the thickness direction of the fixing belt. By providing such an intermediate region, it is possible to suppress abrupt changes in the thermal conductivity, surface properties, and hardness in the longitudinal direction of the elastic layer caused by the difference in the orientation state of the filler between the central region 4c and the end region 4a. It is preferable that the intermediate region 4b is provided in contact with each of the central region 4c and the end region 4a.
[0017] FIG. 3 is a conceptual diagram for explaining the filler orientation in each of the end region 4a, the middle region 4b, and the longitudinal center region 4c. The anisotropy of the thermal conductivity changes mainly due to the change in the orientation of the small particle size filler depending on the region in the longitudinal direction. A method for quantifying the filler orientation will be described later.
[0018] The elastic layer of the fixing member can be manufactured by, for example, a method as shown in FIG. 4. Specifically, an elastic layer made of a silicone polymer containing a thermally conductive filler is formed on a substrate by ring coating or the like. Then, before the elastic layer is heated and cured, the surface of the elastic layer in the longitudinal center region corresponding to the paper passing region is charged, and the elastic layer is heated and cured to fix the filler. By applying an electric field to the elastic layer, the filler mainly moves due to electrophoresis and the force of dipole interaction due to dielectric polarization, and the filler is oriented and arranged in the thickness direction as shown in FIG. 3(c) to form a heat transfer path, thereby increasing the thermal conductivity in the thickness direction.
[0019] In the longitudinal central region 4c to which an electric field is applied, small particle size fillers 8 having a circle equivalent diameter of less than 5 μm among the thermally conductive fillers contained in the composition layer before the thermal curing of the elastic layer 4 are aligned in the thickness direction of the composition layer. On the other hand, large particle size fillers 7 having a circle equivalent diameter of 5 μm or more among the thermally conductive fillers contained in the composition layer are hardly aligned. The composition layer is then heated and cured to form the elastic layer according to this embodiment. The elastic layer thus obtained can further increase the thermal conductivity in the thickness direction of the elastic layer while suppressing the increase in hardness of the elastic layer due to the increase in the amount of filler.
[0020] The reason why the alignment of the large particle size filler 7 in the composition layer is suppressed and the small particle size filler 8 is highly aligned when the outer surface of the composition layer is charged will be described below. It is considered that in the method of FIG. 4, a sufficient force for dielectrophoresis of the large particle size filler 7 does not act. However, it is considered that dielectric polarization occurs in the large particle size filler 7 by charging the surface of the composition layer, and a local electric field is formed between the large particle size fillers 7. As a result, it is considered that the small particle size filler 8 present between the large particle size fillers is highly aligned between the large particle size fillers by the local electric field, and a heat conduction path that connects the large particle size fillers 7 to each other in the thickness direction of the elastic layer is formed.
[0021] A non-contact method is preferred as a method for charging the outer surface of the composition layer, and a method using a corona charger 200 that can easily and inexpensively perform approximately uniform charging as shown in FIG. 4 is more preferred. The corona charger is shorter than the overall length of the elastic layer in the longitudinal direction to be finally produced and covers the paper passing area, so that only the longitudinal center area of the elastic layer can be selectively charged. In addition, a reciprocating mechanism may be provided that vibrates the corona charger back and forth in the longitudinal direction of the elastic layer at about ±1 to 10 mm and about 1 to 10 Hz while the electric field is applied. By performing such a reciprocating motion, an intermediate area can be formed that suppresses a steep change in thermal conductivity, surface properties, and hardness at the boundary between the area to which the electric field is applied and the area to which the electric field is not applied.
[0022] A specific configuration of the fixing member and the thermal fixing device according to an embodiment of the present disclosure will be described below.
[0023] (1) Overview of the fixing member structure The fixing member of the present embodiment will be described in detail with reference to the drawings. Figures 5(a) and (b) are schematic cross-sectional views showing the fixing member according to the present embodiment. Figure 5(a) shows an example of a fixing member in the form of a belt, and Figure 5(b) shows an example of a fixing member in the form of a roller. In Figures 5(a) and (b), reference numeral 3 indicates a base body, and reference numeral 4 indicates an elastic layer containing silicone rubber that covers the outer peripheral surface of the base body 3. In Figure 5, the radial direction is the thickness direction of the elastic layer, and the front-to-back direction of the paper is the longitudinal direction (width direction).
[0024] Thus, the fixing member according to the present embodiment has a base 3 and an elastic layer 4 containing silicone rubber on the base 3. As shown in these figures, the fixing member can have a surface layer 6 on the outer periphery of the elastic layer 4 containing silicone rubber. An adhesive layer 5 can also be provided between the elastic layer 4 containing silicone rubber and the surface layer 6, in which case the surface layer 6 is fixed to the outer periphery of the elastic layer 4 containing silicone rubber by the adhesive layer 5. All of the fixing members shown in FIG. 5 have an endless shape. An endless shape is a shape that allows the same part to pass through the fixing nip portion multiple times (endlessly) by rotating and moving in the circumferential direction.
[0025] (2) Substrate of fixing member When the fixing member is in the form of a belt as shown in FIG. 5(a), the base 3 can be made of metals such as electroformed nickel sleeves and stainless steel sleeves, or heat-resistant resins such as polyimide. In particular, when the thermal fixing device is of an electromagnetic induction heating type, a base material that can be heated by induction heating is selected, and an alloy mainly composed of nickel or iron is used from the viewpoint of heat generation efficiency. A layer for imparting a function of improving adhesion with the elastic layer can be provided on the outer surface (the surface on the elastic layer side) of the base 3. That is, the elastic layer 4 only needs to be provided on the outer peripheral surface of the base 3, and another layer can be provided between the elastic layer 4 and the base 3. In addition, a layer for imparting a function such as wear resistance or lubricity can be further provided on the inner surface (the surface opposite to the outer surface) of the base 3. In addition, when the base 3 is in the form of a belt, a core is inserted into the inside of the sleeve during the following manufacturing process.
[0026] When the fixing member is in the form of a roller as shown in Fig. 5(b), a core made of a metal such as aluminum or iron or an alloy can be used for the base 3, and it is sufficient if it has the strength to withstand the heat and pressure in the thermal fixing device. In Fig. 5(b), a solid core is used as the base 3, but a hollow core may also be used for the base 3, and a heat source such as a halogen lamp may be provided inside.
[0027] (3-1) Elastic layer containing silicone rubber of fixing member The elastic layer 4 containing silicone rubber in the fixing member of this embodiment functions as a layer that imparts excellent flexibility to follow the unevenness of a recording medium such as paper during fixing. Silicone rubber is preferable because it has high heat resistance that allows it to maintain flexibility even in an environment where the temperature reaches a high temperature of about 240°C in a non-paper passing area. In addition, the silicone rubber is preferably electrically insulating or semiconductive because the surface of the silicone rubber is charged before curing as described below to orient the filler, and electrically insulating or semiconductive is also required as a thermally conductive filler. For example, silicone rubber obtained by curing a silicone polymer as described below can be used as the silicone rubber.
[0028] In the fixing member, the elastic layer 4 containing silicone rubber contains a thermally conductive filler to improve heat transfer properties. The type of filler is selected in consideration of the thermal conductivity, specific heat capacity, density, particle size, shape, relative dielectric constant, etc. of the filler itself. Examples of thermally conductive fillers include inorganic fillers such as alumina, zinc oxide, magnesium oxide, metal silicon, silicon carbide, and silica. These fillers may be used alone or in combination of two or more. Note that metal fillers, carbon fiber fillers, and the like have low electrical resistance and are unlikely to cause dielectric polarization when an electric field is applied, and therefore are not suitable for use alone. However, this does not apply when the electrical resistance can be controlled by performing surface treatment such as forming an oxide film to make it easier to cause dielectric polarization.
[0029] The filler can be surface-treated to enhance its affinity for silicone rubber and to control the electrical resistance value. Specifically, fillers such as alumina, silica, and magnesium oxide that have active groups such as hydroxyl groups on their surfaces can be surface-treated with a silane coupling agent, hexamethyldisilazane, or the like.
[0030] The average particle size of the filler is preferably in the range of 0.1 μm to 100 μm, more preferably in the range of 0.3 μm to 30 μm, where the average particle size refers to the volume average particle size.
[0031] The particle size of the large particle size filler that is not aligned as much as possible is 5 μm or more. It is assumed that a binary image of 150 μm×100 μm size is obtained at any five points on the cross section in the thickness direction and circumferential direction (thickness-circumferential direction) of the elastic layer, and a binary image of the same size is obtained at any five points on the cross section in the thickness direction and longitudinal direction (thickness-longitudinal direction). At this time, the average value of the area ratio (%) of the large particle size filler in each of the total 10 binary images (hereinafter, also referred to as the "average area ratio of the large particle size filler") is preferably 20% or more and 40% or less. Here, the area ratio of the large particle size filler means [(sum of the areas of the large particle size filler in the binary image × 100) / (area of the binary image)]. When the average area ratio of the large particle size filler is 20% or more, the distance between the large particle size fillers is not too long, and a sufficiently large local electric field can be generated when an electric field is applied. Therefore, the small particle size filler particles present between the large particle size fillers can be sufficiently aligned. Also, when the average area ratio of the large particle size filler particles is 40% or less, the hardness of the elastic layer can be sufficiently reduced.
[0032] The particle size of the small particle size filler to be arranged is less than 5 μm. The average area ratio of the small particle size filler in each of the binary images (hereinafter also referred to as the "average area ratio of the small particle size filler") is preferably 10% or more and 20% or less. Here, the area ratio of the small particle size filler means [(total area of the small particle size filler in the binary image x 100) / (area of the binary image)]. When the average area ratio of the small particle size filler is 10% or more, it is easy to arrange the small particle size filler and achieve sufficiently high thermal conductivity. Also, when the average area ratio of the small particle size filler is 20% or less, an increase in the viscosity of the material is suppressed, and it is easy to ensure the processability and smoothness of the elastic layer.
[0033] The sum of the average area ratio of the large particle size filler and the average area ratio of the small particle size filler is preferably 30% or more and 60% or less, particularly 30% or more and 50% or less. The sum of the average area ratio of the large particle size filler and the average area ratio of the small particle size filler is a value that is closely related to the volume ratio of the total filler in the elastic layer. By setting the sum of the average area ratio of the large particle size filler and the average area ratio of the small particle size filler within the above range, it is possible to better achieve both high thermal conductivity of the elastic layer and suppression of high hardness.
[0034] The large particle size filler and the small particle size filler may be blended by blending a filler having a wide particle size distribution, or by blending a filler having a large average particle size and a filler having a small average particle size. In terms of ease of adjusting the average area ratio occupied by the large particle size filler and the small particle size filler to the above range, it is preferable to blend the latter fillers having different average particle sizes.
[0035] The elastic layer containing silicone rubber can be formed by curing a liquid addition-curable silicone rubber composition that contains at least a filler and, for example, a liquid addition-curable silicone rubber component.
[0036] The liquid addition curing silicone rubber can contain (a) an organopolysiloxane having an unsaturated aliphatic group, (b) an organopolysiloxane having active hydrogen bonded to silicon, (c) a catalyst (e.g., a platinum compound), and (d) a cure retarder. (a) functions as a crosslinking point during the curing reaction. (b) is a crosslinking agent. (c) is a catalyst for promoting the curing reaction. (d) is a cure retarder (inhibitor) for controlling the reaction start time. In addition to these, fillers suitable for each purpose can be kneaded and dispersed to impart heat resistance, reinforcing properties, etc. Below, (a) to (d) are explained.
[0037] (a) Organopolysiloxane having an unsaturated aliphatic group Any organopolysiloxane having an unsaturated aliphatic group (hereinafter sometimes referred to as component a) can be used as long as it has an unsaturated aliphatic group such as a vinyl group. For example, the following formulas 1 and 2 can be used as component a.
[0038] ·R 1 R 1 The intermediate unit represented by SiO and R 1 R 2 one or both intermediate units selected from the group consisting of intermediate units represented by SiO and R 1 R 1 R 2 SiO 1 / 2 and a molecular end represented by the following formula 1.
[0039] [ka]
[0040] ·R 1 R 1 The intermediate unit represented by SiO and R 1 R 2 one or both intermediate units selected from the group consisting of intermediate units represented by SiO and R 1 R 1 R 1 SiO 1 / 2 and a molecular end represented by the following formula 2.
[0041] [ka]
[0042] (In Equation 1 and Equation 2, R 1 each independently represents an unsubstituted hydrocarbon group that does not contain an unsaturated aliphatic group, R 2 each independently represents an unsaturated aliphatic group, and m and n each independently represent an integer of 0 or more.
[0043] In addition, in Equation 1 and Equation 2, R 1 Examples of the unsubstituted hydrocarbon group not containing an unsaturated aliphatic group include an alkyl group (such as a methyl group, an ethyl group, a propyl group, etc.) and an aryl group (such as a phenyl group, etc.). In particular, a methyl group is preferable.
[0044] In addition, in Equation 1 and Equation 2, R 2 Examples of the unsaturated aliphatic group represented by the formula (I) include a vinyl group, an allyl group, and a 3-butenyl group, with a vinyl group being preferred.
[0045] In formula 1, linear organosiloxanes with n=0 have unsaturated aliphatic groups only at both ends, while linear organosiloxanes with n=1 or more have unsaturated aliphatic groups at both ends and in the side chain. The linear organosiloxanes of formula 2 have unsaturated aliphatic groups only in the side chain. The component a may be used alone or in combination of two or more.
[0046] In addition, when component a is used in the elastic layer of the fixing member, the viscosity is set to 100 mm from the viewpoint of moldability. 2 / s or more, 50000mm 2 / s or less. The viscosity (kinetic viscosity) can be measured using a capillary viscometer, a rotational viscometer, or the like based on JIS Z 8803:2011. When using a commercially available component a, the catalog value can be referred to.
[0047] (b) Organopolysiloxane having active hydrogen bonded to silicon (crosslinking agent) Organopolysiloxane having active hydrogen bonded to silicon (hereinafter sometimes referred to as component B) is a crosslinking agent that forms a crosslinked structure by reacting with the unsaturated aliphatic groups in component A through the catalytic action of a platinum compound.
[0048] Any organopolysiloxane having a Si-H bond can be used as component b, but for example, those that meet the following requirements can be suitably used. Note that component b can be used alone or in combination of two or more types.
[0049] From the viewpoint of forming a crosslinked structure by reaction with organopolysiloxane having an unsaturated aliphatic group, the number of hydrogen atoms bonded to silicon atoms is an average of 3 or more per molecule (Si-H bonds may be present in any siloxane unit in the molecule). The organic group bonded to the silicon atom is, for example, an unsubstituted hydrocarbon group as described above (the unsubstituted hydrocarbon group is preferably a methyl group). The siloxane skeleton (-Si-O-Si-) can be linear, branched or cyclic.
[0050] For example, the linear organopolysiloxanes shown in the following formulas 3 and 4 can be used as component b.
[0051] [ka]
[0052] [ka]
[0053] (In Equation 3 and Equation 4, R 1 each independently represents an unsubstituted hydrocarbon group not containing an unsaturated aliphatic group, p represents an integer of 0 or more, and q represents an integer of 1 or more.
[0054] In addition, R 1 As explained in Formula 1 and Formula 2, is an unsubstituted hydrocarbon group that does not contain an unsaturated aliphatic group, and is preferably a methyl group.
[0055] (c) Catalyst As the hydrosilylation (addition curing) catalyst, for example, a platinum compound can be used. Specific examples include platinum carbonylcyclovinylmethylsiloxane complex, 1,3-divinyltetramethyldisiloxane platinum complex, etc. Hereinafter, this may be referred to as component c.
[0056] (d) Hardening retarder In order to adjust the curing reaction speed of hydrosilylation (addition curing), a curing retarder can be added. Specific examples include 2-methyl-3-butyn-2-ol and 1-ethynyl-1-cyclohexanol. Hereinafter, this curing retarder may be referred to as component d.
[0057] The elastic modulus of the silicone rubber-containing elastic layer can be adjusted to some extent by the types and amounts of the components a to d. It is more preferable that the silicone rubber-containing elastic layer has a (tensile) elastic modulus of 0.20 MPa or more and 1.20 MPa or less. If the elastic modulus of the elastic layer is within this range, the elastic layer has low hardness (flexibility), and high-quality images can be obtained.
[0058] The composition of the silicone rubber contained in the elastic layer can be confirmed by performing attenuated total reflection (ATR) measurement using an infrared spectrometer (FT-IR) (for example, product name: Frontier FT IR, manufactured by PerkinElmer). The silicon-oxygen bond (Si-O), which is the main chain structure of silicone, has a wave number of 1020 cm due to stretching vibration. -1 In addition, the methyl group bonded to the silicon atom (Si-CH 3 ) is a bending vibration caused by its structure, and has a wave number of 1260 cm -1 Its presence can be confirmed by the strong infrared absorption in the vicinity.
[0059] The content of the cured silicone rubber and filler in the elastic layer can be confirmed by using a thermogravimetric analyzer (TGA) (for example, product name: TGA851, manufactured by Mettler-Toledo). The elastic layer is cut out with a razor or the like, and about 20 mg is accurately weighed and placed in an alumina pan used in the device. The alumina pan containing the sample is set in the device and heated from room temperature to 800°C at a rate of 20°C per minute in a nitrogen atmosphere, and then kept at 800°C for one hour. In a nitrogen atmosphere, the cured silicone rubber component is decomposed and removed by cracking without being oxidized as the temperature rises, so the weight of the sample decreases. By comparing the weight before and after the measurement, the content of the cured silicone rubber component and the content of the filler contained in the elastic layer can be confirmed.
[0060] (3-2) Step of applying an electric field to the elastic layer Hereinafter, a corona charger 200 and a process of applying an electric field to an elastic layer using the corona charger will be described as an embodiment. Corona charging methods include a scorotron method having a grid electrode between the corona wire and the body to be charged, and a corotron method not having a grid electrode. From the viewpoint of controllability of the surface potential of the body to be charged, the scorotron method is preferred.
[0061] 4(a) and (b), the corona charger 200 includes a front block 201, a rear block 202, and shields 203 and 204. A discharge wire 205 is stretched between the front block 201 and the rear block 202. When a charging bias is applied from a high-voltage power supply, the discharge occurs and charges the surface of the uncured elastic layer 4 on the substrate as the body to be charged.
[0062] Similar to the configuration of a general corona charger, a high voltage is applied to a discharge wire 205 serving as a discharge member. An ion flow obtained by discharge to the shields 203 and 204 is controlled by applying a high voltage to the grid 206, and the surface of the elastic layer 4 is controlled to a desired charged potential. At this time, since the base 3 or the core 1 holding the base 3 is grounded (not shown), it is possible to generate a desired electric field in the elastic layer 4 by controlling the surface potential of the surface of the elastic layer 4.
[0063] The manufacturing method of the fixing member of the above embodiment will be described in detail. First, an uncured elastic layer having silicone rubber containing a thermally conductive filler is formed on a substrate. Next, as shown in FIG. 4(a), a corona charger 200 is arranged to face the uncured elastic layer 4 of the fixing member 100 in the width direction in close proximity. Then, a voltage is applied to the grid 206 of the corona charger 200, and the fixing member 100 is rotated in a discharged state, thereby charging the surface of the elastic layer 4. By charging the surface of the elastic layer 4 in this way, an electric field is generated in the elastic layer, which orients the thermally conductive filler. After that, the elastic layer is cured by heating or the like, and the orientation of the filler is fixed.
[0064] The voltage applied to the grid 206 is preferably in the range of 0.1 kV to 3 kV (0.2 to 6 kV in Vp-p in the case of AC application) in terms of generating an effective electrostatic interaction in the filler. When forming the filler orientation in the thickness direction of the elastic layer using an electric field, it is important to generate an electric field in the thickness direction of the elastic layer 4. If the sign of the applied voltage is equal to the sign of the voltage applied to the wire, the direction of the electric field will be reversed whether it is negative or positive, but the effect obtained is the same. In addition, when AC charging is performed to suppress the liquid surface flow described later, it is desirable to match the phase of the waveform of the wire and the grid. Depending on the type of thermally conductive filler, it may be difficult to form the orientation of the amorphous filler, in which case it is desirable to increase the voltage applied to the grid 206. It is presumed that this is related to the dielectric constant of the silicone rubber component and the thermally conductive filler. When the dielectric constant difference between the silicone rubber and the filler is large, it is possible to form the orientation of the amorphous filler with a relatively small applied voltage. On the other hand, if the voltage applied to the grid 206 is too large, the electrostatic repulsive force due to the surface charge of the elastic layer becomes large, causing the liquid surface to flow, which may deteriorate the surface properties of the elastic layer 4. Therefore, the voltage applied to the grid 206 is more preferably in the range of 0.1 kV to 1.5 kV in absolute value (0.2 to 3 kV in Vp-p in the case of AC application). This liquid surface flow can be alleviated by applying AC charging.
[0065] As a configuration for controlling the potential in the longitudinal direction of the elastic layer surface, for example, the configuration shown in FIG. 4(a) can be used, and while a voltage is applied to the grid 206, the central axis of the core 1 inserted in the fixing member 100 is rotated as the rotation axis. In this way, it is possible to charge the elastic layer 4 almost uniformly all around in the circumferential direction. The rotation speed of the fixing member is preferably 10 rpm to 500 rpm, and the treatment time is preferably 20 seconds or more from the viewpoint of stably forming the orientation of the filler. As described above, the formation of the orientation of the irregular filler can be controlled by controlling the surface potential and the time for applying the electric field.
[0066] The intermediate region 4b can be formed by making the charge amount at the position corresponding to the intermediate region of the untreated elastic layer intermediate between the charge amounts of the region corresponding to the central region and the region corresponding to the end region. Specifically, for example, as shown in FIG. 4(a), the discharge width of the corona charger is made shorter than the length L of the elastic layer in the longitudinal direction of the treated object. This corona charger is vibrated back and forth in the longitudinal direction of the untreated elastic layer, which is the treated object, for example, by about ±1 to 10 mm and at a frequency of about 1 to 10 Hz using a reciprocating mechanism (not shown). This makes it possible to make the charge amount of the surface of the untreated elastic layer be the region corresponding to the central region>the region corresponding to the intermediate region>the region corresponding to the end region.
[0067] Although stainless steel, nickel, molybdenum, tungsten, etc. may be used as the discharge wire 205, it is preferable to use tungsten, which is a very stable metal. The discharge wire stretched inside the shield may have a circular cross section or a sawtooth cross section.
[0068] Moreover, the diameter of the discharge wire 205 is preferably 40 μm to 100 μm. By setting the diameter of the discharge wire within this range, it is possible to prevent the discharge wire from being cut by ions during discharge, and it is also possible to eliminate the need to make the voltage required to generate a corona discharge excessively high. Either a DC voltage or an AC voltage can be used as the voltage applied to the discharge wire 205. In the case of an AC voltage, it is preferable that the frequency is about 0.01 Hz to 1000 Hz. The voltage can be generated by outputting a square wave, a sine wave, or the like, using an arbitrary waveform generator.
[0069] From the viewpoint of making the electrostatic potential on the surface of the elastic layer more uniform, it is preferable that the width of the multiple openings (through holes) penetrating the grid in a mesh shape is etched to a shape pattern including 1.0 mm or less. Also, the higher the area ratio of the mesh portion to the through hole portion, the easier it is to make the electrostatic potential uniform. The flat grid 206 can be disposed between the discharge wire 205 and the surface of the elastic layer, and from the viewpoint of making the electrostatic potential on the surface of the elastic layer uniform, it is preferable that the distance between the elastic layer surface and the grid 206 is in the range of 1 mm to 10 mm.
[0070] (3-3) Confirmation of the arrangement of thermally conductive fillers in the elastic layer The alignment state of the thermally conductive filler can be confirmed by performing a two-dimensional Fourier transform using a binarized image obtained from a cross-sectional image of the elastic layer.
[0071] First, a measurement sample is prepared. For example, when the fixing member is a fixing belt 400 as shown in FIG. 6(a), as shown in FIG. 6(b), for example, 10 samples 401 each having a length of 5 mm, a width of 5 mm, and a thickness of the entire thickness of the fixing belt are taken from 10 arbitrary positions in each of the longitudinal center region and end region of the fixing belt, and in the intermediate region if there is an intermediate region. FIG. 6(a) shows a form in which a sample 401a is taken from the end region, and a sample 401c is taken from the longitudinal center region. For five samples out of the obtained 10 samples, the cross section in the circumferential direction of the fixing belt, that is, the cross section including the first cross section 401-1 in the thickness-circumferential direction of the elastic layer, is polished using an ion beam. For the remaining five samples, the cross section in the direction perpendicular to the circumferential direction of the fixing belt, that is, the cross section including the second cross section 401-2 in the thickness-longitudinal direction of the elastic layer, is polished using an ion beam. For polishing the cross section using an ion beam, for example, a cross-section polisher can be used. Polishing the cross section with an ion beam can prevent the filler from falling off the sample and the abrasive from getting mixed in, and can also form a cross section with fewer polishing marks.
[0072] Next, five samples each of the polished first and second cross sections of the elastic layer are observed using a laser microscope or a scanning electron microscope (SEM), and cross-sectional images of an area of 150 μm x 100 μm are obtained (Figure 7(a)).
[0073] Next, the obtained image is binarized using commercially available image software so that the filler part is white and the silicone rubber part is black (Fig. 7(b)). As a binarization method, for example, the Otsu method can be used.
[0074] Next, the circle equivalent diameter is calculated for each filler in the obtained binarized image, and the image is divided into an image in which only large particle size fillers 7 with a circle equivalent diameter of 5 μm or more remain (FIG. 7(c)), and an image in which only small particle size fillers 8 with a circle equivalent diameter of less than 5 μm remain (FIG. 7(d)). Then, the area ratio of the large particle size fillers 7 and the small particle size fillers 8 (the ratio of the total area of each filler 7, 8 to the total area of the image) is calculated from each image. The circle equivalent diameter of each filler refers to the diameter of a circle having the same area as the area of the filler in question.
[0075] Furthermore, by performing two-dimensional Fourier transform analysis on the large particle size filler image and the small particle size filler image, an elliptical plot diagram showing the direction and degree of filler arrangement can be obtained (Fig. 7(e) and Fig. 7(f) respectively). Because the two-dimensional Fourier transform itself has a peak in the direction perpendicular to the periodicity of the binary image, the elliptical plot diagram is the result of shifting the phase of the two-dimensional Fourier transform result by 90°. The arrangement angle Φ can be calculated from the angle made by the semi-major axis of this elliptical plot diagram, and the filler arrangement degree f, defined as f=1-(y / x) when the semi-major axis is x and the semi-minor axis is y, can be calculated. The arrangement angle Φ represents the arrangement direction of the filler, and in Figures 7(e) and 7(f), the 90°-270° direction represents the thickness direction of the elastic layer, and the 0°-180° direction represents the circumferential direction or axial direction of the elastic layer. Therefore, the closer the arrangement angle Φ is to 90°, the more the filler is arranged in the thickness direction. Additionally, the degree of alignment f represents the flattening of the ellipse and is a value between 0 and 1. When f is 0, it becomes a circle, representing a completely random state with no alignment, and as f approaches 1, the flattening of the ellipse becomes greater, and the degree of alignment of the filler also increases. The filler arrangement angle Φ and the degree of arrangement f are calculated as the average values of 10 locations in total, 5 locations on each of the first cross section in the thickness-circumferential direction of the elastic layer and the second cross section in the thickness-longitudinal direction.
[0076] The average alignment degree of the large particle size filler is f L If so, f L is preferably 0.00 or more and 0.15 or less. LBy making the hardness of the elastic layer 0.15 or less, it is possible to achieve a low hardness.
[0077] The average arrangement angle of the large particle size filler is Φ L In this case, Φ L can be any value between 0° and 180°.
[0078] The average arrangement angle of the small particle size filler is Φ S In this case, Φ S is preferably 60° or more and 120° or less. S The direction where the angle is 90° is the thickness direction of the elastic layer, so Φ S The closer to 90°, the more the particles are aligned in the thickness direction. S By keeping Φ in the above range, the thermal conductivity in the thickness direction can be increased. S is preferably 30° or less or 150° or more. Here, 30° and 150° are in a mirror image relationship with respect to the boundary of 90°, and therefore have the same heat transfer function in the thickness direction. In the intermediate region, the average arrangement angle Φ of the small particle size filler is between the longitudinal center region and the end region. S It is preferable that the angle is greater than 30° and less than 60°, or greater than 120° and less than 150°.
[0079] (4) Adhesive layer of fixing member As shown in FIG. 5, the adhesive layer 5 is a layer formed by adhering the elastic layer 4 and the surface layer (release layer) 6 with, for example, an addition-curing silicone rubber adhesive. It is preferable to use an addition-curing silicone rubber containing a self-adhesive component as the adhesive. Specifically, it contains an organopolysiloxane having a plurality of unsaturated aliphatic groups, typically vinyl groups, in the molecular chain, a hydrogenorganopolysiloxane, and a platinum compound as a crosslinking catalyst. It hardens by an addition reaction. Any known adhesive can be used as such an adhesive.
[0080] Examples of self-adhesive components include: silanes having at least one functional group, preferably two or more functional groups, selected from the group consisting of an alkenyl group such as a vinyl group, a (meth)acryloxy group, a hydrosilyl group (SiH group), an epoxy group, an alkoxysilyl group, a carbonyl group, and a phenyl group; Organosilicon compounds such as cyclic or linear siloxanes having 2 to 30 silicon atoms, preferably 4 to 20 silicon atoms; A non-silicon-based (i.e., silicon-free) organic compound that may contain oxygen atoms in the molecule, provided that it contains 1 to 4, preferably 1 to 2, aromatic rings such as phenylene structures having a valence of 1 to 4, preferably valence of 2 to 4, in one molecule, and at least 1, preferably 2 to 4, functional groups capable of contributing to a hydrosilylation addition reaction (e.g., alkenyl groups, (meth)acryloxy groups) in one molecule. The above self-adhesive components may be used alone or in combination of two or more.
[0081] From the viewpoint of adjusting the viscosity and ensuring heat resistance, a filler component may be added to the adhesive within the scope of the present invention. Examples of the filler component include the following. Silica, alumina, iron oxide, titanium oxide, cerium oxide, cerium hydroxide, carbon black, etc. Such addition curing type silicone rubber adhesives are commercially available and are easily available.
[0082] The thickness of the adhesive layer is preferably 20 μm or less. By setting the thickness to 20 μm or less, the thermal resistance of the fixing member can be set small, and heat from the inner surface side (substrate side) can be efficiently transferred to the recording material (recording medium).
[0083] (5) Surface layer of fixing member The surface layer 6 is made of a fluororesin, and a tube method or a coating method is used as a molding method. The following describes the tube method, in which a resin exemplified below is molded into a tube shape and then coated. Tetrafluoroethylene-perfluoro(alkyl vinyl ether) copolymer (PFA), polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), etc. Among the resin materials listed above, PFA is preferred from the viewpoints of moldability and toner releasability. The thickness of the fluororesin layer (surface layer) is preferably 10 μm or more and 50 μm or less, because this maintains the elasticity of the lower elastic layer when laminated, and can ensure abrasion resistance while preventing the surface hardness as a fixing member from becoming too high. The inner surface of the fluororesin tube can be preliminarily treated with sodium, excimer laser, ammonia, or the like to improve the adhesiveness.
[0084] 8 is a schematic diagram of an example of a process for laminating a surface layer 6 via an addition-curing silicone rubber adhesive on an elastic layer 4 containing silicone rubber. An addition-curing silicone rubber adhesive 5 is applied to the surface of the elastic layer 4 formed on the outer circumferential surface of a substrate 3. Furthermore, a fluororesin tube is coated on the outer surface of the adhesive 5 as the surface layer 6 and laminated. The method for covering the fluororesin tube is not particularly limited, but may be a method of covering with an addition-curing silicone rubber adhesive as a lubricant, or a method of expanding and covering the fluororesin tube from the outside. The excess addition-curing silicone rubber adhesive 5 remaining between the elastic layer 4 and the surface layer 6 made of the fluororesin tube is removed by squeezing it out using a means not shown. From the viewpoint of heat transfer, it is preferable that the thickness of the adhesive layer 5 after being squeezed out is 20 μm or less. Next, the addition-curing silicone rubber adhesive 5 is cured and adhered by heating for a predetermined period of time using a heating means such as an electric furnace, and both ends in the longitudinal direction (width direction) are cut to the desired length to obtain the fixing member.
[0085] (6) Heat fixing device The thermal fixing device according to the present embodiment is configured so that a pair of heated rollers, belts, or other rotating bodies are pressed against each other. The type of thermal fixing device is appropriately selected in consideration of the overall process speed, size, and other conditions of the image forming apparatus in which the thermal fixing device is mounted. In a thermal fixing device, a fixing nip N is formed by pressing a heated fixing member and a pressure member, and a recording medium S, which is a heated body and has an image formed with unfixed toner, is sandwiched and conveyed through this fixing nip N. The image formed with the unfixed toner is called a toner image t. In this way, the toner image t is heated and pressurized. As a result, the toner image t is melted and mixed, and then cooled to fix the image on the recording medium.
[0086] A specific example of the thermal fixing device will be given below to explain its configuration, but the scope and applications of the present invention are not limited to this example.
[0087] (6-1) Fixing belt-pressure belt type heat fixing device FIG. 9 is a schematic cross-sectional view of an example of a thermal fixing device having a fixing belt as a fixing member, which is a so-called twin-belt type thermal fixing device in which a pair of rotating bodies, namely a fixing belt 11 and a pressure belt 12, are in pressure contact with each other. It should be noted that the longitudinal direction (width) of the thermal fixing device or the components that make it up is the direction perpendicular to the plane of the paper in Figure 9. The front of the thermal fixing device is the side where the recording medium S is introduced. Left and right are left and right when viewed from the front of the device. The belt width is the belt dimension in the left-right direction when viewed from the front of the device. The width of the recording medium S is the dimension of the recording medium in a direction perpendicular to the transport direction. Additionally, upstream and downstream are upstream and downstream in relation to the transport direction of the recording medium. This thermal fixing device includes fixing members, a fixing belt 11 and a pressure belt 12. The fixing belt 11 and the pressure belt 12 are each a fixing belt including a flexible base made of a metal whose main component is nickel, as shown in Fig. 5(a), stretched over two rollers.
[0088] The heating means for the fixing belt 11 is a heating source (induction heating member, excitation coil) capable of heating by energy-efficient electromagnetic induction heating. The induction heating member 13 is composed of an induction coil 13a, an excitation core 13b, and a coil holder 13c that holds them. The induction coil 13a uses a Litz wire wound flat in an oval shape, and is placed inside a horizontal E-shaped excitation core 13b that protrudes from the center and both sides of the induction coil. The excitation core 13b uses a material with high magnetic permeability and low residual magnetic velocity density, such as ferrite or permalloy, so that loss in the induction coil 13a and excitation core 13b can be suppressed, and the fixing belt 11 can be heated efficiently.
[0089] When a high-frequency current is applied from the excitation circuit 14 to the induction coil 13a of the induction heating member 13, the base of the fixing belt 11 is inductively heated, and the fixing belt 11 is heated from the base side. The surface temperature of the fixing belt 11 is detected by a temperature detection element 15 such as a thermistor. A signal related to the temperature of the fixing belt 11 detected by this temperature detection element 15 is sent to a control circuit unit 16. The control circuit unit 16 controls the power supplied from the excitation circuit 14 to the induction coil 13a so that the temperature information received from the temperature detection element 15 is maintained at a predetermined fixing temperature, thereby adjusting the temperature of the fixing belt 11 to the predetermined fixing temperature.
[0090] The fixing belt 11 is stretched around a roller 17 as a belt rotating member and a heating side roller 18. The roller 17 and the heating side roller 18 are supported by bearings between left and right side plates (not shown) of the device so as to be freely rotatable.
[0091] Roller 17 is, for example, a hollow iron roller having an outer diameter of 20 mm, an inner diameter of 18 mm, and a thickness of 1 mm, and functions as a tension roller that applies tension to fixing belt 11. Heating side roller 18 is, for example, a highly slidable elastic roller having an outer diameter of 20 mm, an inner diameter of 18 mm, an iron alloy core metal, and a silicone rubber layer as an elastic layer.
[0092] This heating side roller 18, as a drive roller, receives a driving force from a drive source (motor) M via a drive gear train (not shown), and is driven to rotate in the clockwise direction of the arrow at a predetermined speed. By providing this heating side roller 18 with an elastic layer as described above, the driving force input to the heating side roller 18 can be effectively transmitted to the fixing belt 11, and a fixing nip can be formed to ensure separation of the recording medium from the fixing belt 11. By providing the heating side roller 18 with an elastic layer, heat conduction to the heating side roller is also reduced, which is also effective in shortening the warm-up time.
[0093] When the heating side roller 18 is driven to rotate, the fixing belt 11 rotates together with the roller 17 due to friction between the silicone rubber surface of the heating side roller 18 and the inner surface of the fixing belt 11. The arrangement and size of the roller 17 and the heating side roller 18 are selected according to the size of the fixing belt 11. For example, the dimensions of the roller 17 and the heating side roller 18 are selected so that the fixing belt 11, which has an inner diameter of 55 mm when not installed, can be stretched over them.
[0094] The pressure belt 12 is tensioned by a tension roller 19 and a pressure side roller 20, which serve as belt rotation members. The inner diameter of the pressure belt when not attached is, for example, 55 mm. The tension roller 19 and the pressure side roller 20 are supported by bearings that are freely rotatable between the left and right side plates (not shown) of the device.
[0095] The tension roller 19 is, for example, an iron alloy core having an outer diameter of 20 mm and an inner diameter of 16 mm, and is provided with a silicone sponge layer to reduce heat conduction from the pressure belt 12 by reducing thermal conductivity.
[0096] The pressure side roller 20 is, for example, a low-sliding rigid roller made of an iron alloy having an outer diameter of 20 mm, an inner diameter of 16 mm, and a thickness of 2 mm. The dimensions of the tension roller 19 and the pressure side roller 20 are also selected according to the dimensions of the pressure belt 12.
[0097] Here, in order to form a nip portion N between the fixing belt 11 and the pressure belt 12, the pressure side roller 20 is pressed toward the heating side roller 18 with a predetermined pressure force in the direction of arrow F by a pressure mechanism not shown in the figure at both left and right ends of the rotating shaft.
[0098] In addition, a pressure pad is used to obtain a wide nip portion N without increasing the size of the device. That is, a fixing pad 21 is a first pressure pad that presses the fixing belt 11 toward the pressure belt 12, and a pressure pad 22 is a second pressure pad that presses the pressure belt 12 toward the fixing belt 11. The fixing pad 21 and the pressure pad 22 are supported and disposed between left and right side plates (not shown) of the device. The pressure pad 22 is pressed toward the fixing pad 21 with a predetermined pressure force by a pressing mechanism (not shown) in the direction of the arrow G. The fixing pad 21, which is the first pressure pad, has a pad base and a sliding sheet (low friction sheet) 23 that contacts the belt. The pressure pad 22, which is the second pressure pad, also has a pad base and a sliding sheet 24 that contacts the belt. This is because there is a problem that the portion of the pad that rubs against the inner circumferential surface of the belt is worn down significantly. By interposing the sliding sheets 23 and 24 between the belt and the pad base, wear on the pad can be prevented and sliding resistance can be reduced, ensuring good belt running performance and durability. The fixing belt is provided with a non-contact static electricity removing brush (not shown), and the pressure belt is provided with a contact static electricity removing brush (not shown).
[0099] The control circuit unit 16 drives the motor M at least when image formation is being performed. This causes the heating side roller 18 to rotate, and the fixing belt 11 to rotate in the same direction. The pressure belt 12 rotates following the fixing belt 11. Here, the most downstream portion of the fixing nip is configured to sandwich the fixing belt 11 and the pressure belt 12 between the roller pair 18, 20 for transport, thereby preventing the belts from slipping. The most downstream portion of the fixing nip is the portion where the pressure distribution (recording medium transport direction) in the fixing nip is maximum.
[0100] When the fixing belt 11 is heated to a predetermined fixing temperature and maintained at that temperature (called temperature control), the recording medium S having the unfixed toner image t is conveyed to the nip N between the fixing belt 11 and the pressure belt 12. The recording medium S is introduced with the surface carrying the unfixed toner image t facing the fixing belt 11. Then, the unfixed toner image t of the recording medium S is conveyed while being sandwiched and conveyed while being in close contact with the outer peripheral surface of the fixing belt 11, so that heat is applied from the fixing belt 11 and the unfixed toner image t is fixed to the surface of the recording medium S by receiving a pressure force. At this time, the heat from the heated base of the fixing belt 11 is efficiently transported to the recording medium S through an elastic layer having high thermal conductivity in the thickness direction. After that, the recording medium S is separated from the fixing belt by a separating member 25 and conveyed.
[0101] (6-2) Fixing belt-pressure roller type thermal fixing device FIG. 10 is a schematic diagram showing an example of a fixing belt-pressure roller type thermal fixing device using a ceramic heater as a heating body. In FIG. 10, 11 is a cylindrical or endless fixing belt, and the one described above is used. There is a heat-resistant and heat-insulating belt guide 30 for holding this fixing belt 11. Also, at a position where it comes into contact with the fixing belt 11 (almost at the center of the lower surface of the belt guide 30), a ceramic heater 31 for heating the fixing belt 11 is fitted into a groove formed along the guide length and fixed and supported. The fixing belt 11 is loosely fitted around the belt guide 30. Also, a pressure rigid stay 32 is inserted inside the belt guide 30.
[0102] On the other hand, a pressure roller 33 is disposed facing the fixing belt 11. In this example, the pressure roller is an elastic pressure roller, that is, a core metal 33a is provided with an elastic layer 33b of silicone rubber to reduce hardness, and both ends of the core metal 33a are rotatably supported by bearings between the front and rear chassis side plates (not shown) of the device. The elastic pressure roller is covered with a PFA (tetrafluoroethylene / perfluoroalkyl ether copolymer) tube to improve surface properties.
[0103] Pressure springs (not shown) are respectively compressed between both ends of the pressure rigid stay 32 and spring bearing members (not shown) on the device chassis side, so that a downward force acts on the pressure rigid stay 32. As a result, the lower surface of the ceramic heater 31 disposed on the lower surface of the heat-resistant resin belt guide member 30 and the upper surface of the pressure roller 33 are in pressure contact with each other with the fixing belt 11 sandwiched therebetween, forming a fixing nip portion N.
[0104] The pressure roller 33 is driven to rotate counterclockwise as indicated by an arrow by a driving means (not shown). A rotational force acts on the fixing belt 11 due to friction between the outer surfaces of the pressure roller 33 and the fixing belt 11 caused by the rotational drive of the pressure roller 33. The fixing belt 11 rotates clockwise as indicated by an arrow around the outside of the belt guide 30 at a circumferential speed that corresponds approximately to the rotational circumferential speed of the pressure roller 33, while its inner surface slides in close contact with the lower surface of the ceramic heater 31 at the fixing nip portion N (pressure roller drive method).
[0105] Based on a print start signal, the pressure roller 33 starts to rotate, and the ceramic heater 31 starts to heat up. The rotational circumferential speed of the fixing belt 11 due to the rotation of the pressure roller 33 becomes steady. After that, the temperature of the temperature detection element 34 provided on the upper surface of the ceramic heater rises to a predetermined temperature, for example, 180° C. At that moment, the recording medium S carrying the unfixed toner image t as the heated material is introduced between the fixing belt 11 and the pressure roller 33 in the fixing nip portion N with the toner image carrying surface side facing the fixing belt 11. Then, the recording medium S is in close contact with the lower surface of the ceramic heater 31 via the fixing belt 11 in the fixing nip portion N, and moves through the fixing nip portion N together with the fixing belt 11. During the movement and passing process, the heat of the fixing belt 11 is applied to the recording medium S, and the toner image t is heated and fixed on the surface of the recording medium S. The recording medium S that has passed through the fixing nip portion N is separated from the outer surface of the fixing belt 11 and conveyed.
[0106] The ceramic heater 31 as a heating element is a horizontally elongated linear heating element with low heat capacity, with the longitudinal direction perpendicular to the moving direction of the fixing belt 11 and the recording medium S. It is preferable that the basic configuration is a heater substrate 31a made of aluminum nitride or the like, a heat generation layer 31b provided on the surface of the heater substrate 31a along its longitudinal direction, and a protective layer 31c of glass, fluororesin, or the like provided thereon. The heat generation layer 31b can be provided by applying an electric resistance material such as Ag / Pd (silver / palladium) to a thickness of about 10 μm and a width of 1 to 5 mm by screen printing or the like. However, the ceramic heater used is not limited to this. When a current is applied between both ends of the heat generating layer 31b of the ceramic heater 31, the heat generating layer 31b generates heat, and the temperature of the ceramic heater 31 rises rapidly.
[0107] The ceramic heater 31 is fixedly supported by being fitted with the protective layer 31c side facing upward into a groove formed along the longitudinal direction of the belt guide 30 at approximately the center of the underside of the belt guide 30. In the fixing nip N that contacts the fixing belt 11, the surface of the sliding member 31d of the ceramic heater 31 and the inner surface of the fixing belt 11 come into sliding contact with each other. In this way, the heater heats the base of the fixing member, and the heat is further applied to the recording medium S via the elastic layer on the base.
[0108] As described above, the elastic layer containing silicone rubber has high thermal conductivity in the thickness direction and low hardness in the fixing belt 11. With this configuration, the fixing belt 11 can efficiently heat an unfixed toner image and has low hardness, so that a high-quality image can be fixed onto the recording medium S at the fixing nip.
[0109] As described above, according to one aspect of the present disclosure, a thermal fixing device including a fixing member is provided, and therefore, it is possible to provide a thermal fixing device including a fixing member having excellent fixing performance and image quality. EXAMPLES
[0110] The present disclosure will be specifically described below using examples, but the present disclosure is not limited to these examples.
[0111] (1) Preparation of liquid addition-curable silicone rubber composition First, 98.6 parts by mass of a silicone polymer having vinyl groups, which are unsaturated aliphatic groups, only at both ends of the molecular chain and having methyl groups as unsubstituted hydrocarbon groups containing no other unsaturated aliphatic groups, was prepared as component a. This silicone polymer (trade name: DMS-V35, manufactured by Gelest, viscosity 5000 mm 2 / s) will be referred to as "Vi" from here on. Next, 170 parts by mass of metal silicon (product name: #350, manufactured by Kinsei Matec Co., Ltd.) was added as a thermally conductive filler to this Vi and thoroughly mixed to obtain mixture 1. Next, 0.2 parts by mass of 1-ethynyl-1-cyclohexanol (manufactured by Tokyo Chemical Industry Co., Ltd.), a cure retarder as component d, dissolved in the same weight of toluene was added to mixture 1 to obtain mixture 2. Next, 0.1 parts by mass of a hydrosilylation catalyst (platinum catalyst: a mixture of 1,3-divinyltetramethyldisiloxane platinum complex, 1,3-divinyltetramethyldisiloxane, and 2-propanol) as component c was added to mixture 2 to obtain mixture 3. Furthermore, as component b, a silicone polymer having a linear siloxane skeleton and having active hydrogen groups bonded to silicon only on the side chain (product name: HMS-301, manufactured by Gelest, viscosity 30 mm 2 1.5 parts by mass of dimethylformamide (SiH) was weighed out and added to mixture 3, which was then thoroughly mixed to obtain a liquid addition-curable silicone rubber composition.
[0112] (2) Preparation of the fixing belt A SUS endless belt having an inner diameter of 55 mm, a width of 420 mm, and a thickness of 65 μm was prepared as a substrate. During the series of manufacturing steps, the endless belt was handled with a core inserted therein. A primer (product name: DY39-051A / B; manufactured by Dow Corning Toray Co., Ltd.) was applied approximately uniformly to the outer peripheral surface of the substrate so that the dry weight was 20 mg. After the solvent was dried, the substrate was baked for 30 minutes in an electric furnace set to 160°C. The silicone rubber composition was applied to the primer-treated substrate by ring coating to a thickness of 250 μm, which is referred to as an uncured endless belt.
[0113] Next, a corona charger with a charging area width of 295 mm was placed facing the generator of the uncured endless belt, and an AC electric field was applied to the surface of the elastic layer before curing while rotating the uncured endless belt at 100 rpm. The conditions were: current supplied to the discharge wire of the corona charger was ±150 μA, grid electrode potential was ±300 V (Vp-p: 600 V), frequency was 0.025 Hz, charging time was 160 seconds, and the distance between the grid electrode and the belt was 3 mm.
[0114] This charged uncured endless belt was heated in an electric furnace at 160°C for 1 minute (primary curing), and then heated in an electric furnace at 200°C for 30 minutes (secondary curing) to cure the silicone rubber composition, thereby obtaining an endless belt with a cured elastic layer.
[0115] Next, an addition-curing silicone rubber adhesive (product name: SE1819CV A / B; manufactured by Toray Dow Corning Co., Ltd.) was applied almost uniformly to a thickness of about 20 μm as an adhesive layer on the surface of the cured elastic layer of the endless belt. A fluororesin tube (product name: NSE; manufactured by Gunze Co., Ltd.) with an inner diameter of 53 mm and a thickness of 40 μm was laminated on top of this as a release layer while expanding its diameter. After that, the belt surface was uniformly rubbed from above the fluororesin tube to rub out excess adhesive from between the elastic layer and the fluororesin tube until it became thin, down to about 5 μm. The endless belt was heated for 1 hour in an electric furnace set at 200°C to harden the adhesive and fix the fluororesin tube onto the elastic layer. Both ends of the obtained endless belt were cut to obtain a fixing belt with a width of 368 mm. As a result, the fixing belt had a longitudinal center region that was charged in the region about 0.1 L or more from both ends of the elastic layer in the longitudinal direction (width direction) toward the center, and end regions on both sides of that.
[0116] (3) Evaluation of characteristics of elastic layer of fixing belt (3-1) Thermal conductivity of the elastic layer in the thickness direction The thermal conductivity λnd of the elastic layer in the thickness direction was calculated from the following formula. λnd=α×C p ×ρ In the formula, λnd is the thermal conductivity of the elastic layer in the thickness direction (W / (m K)), α is the thermal diffusivity in the thickness direction (m 2 / s), C p is the specific heat at constant pressure (J / (kg K)), and ρ is the density (kg / m 3 ). Here, the thermal diffusivity α in the thickness direction and the specific heat at constant pressure C p The values of and density ρ were obtained by the following method.
[0117] ·Thermal diffusivity α The thermal diffusivity α in the thickness direction of the elastic layer was measured at room temperature (25°C) using a periodic heating method thermal property measurement device (product name: FTC-1, manufactured by Advance Riko Co., Ltd.). Sample pieces with an area of 8 × 12 mm were cut from the elastic layer with a cutter knife to prepare a total of five sample pieces, and the thickness of each sample piece was measured using a digital length measuring device (product name: DIGIMICRO (registered trademark) MF-501 flat probe φ4 mm; manufactured by Nikon Corporation). Next, a total of five measurements were made for each sample piece, and the average value (m 2 The measurement was performed while applying pressure to the sample piece using a 1 kg weight. As a result, the thermal diffusivity α in the thickness direction of the longitudinal center region of the elastic layer was 9.31×10 -7 m 2 / s, and the thermal diffusivity of the edge region is 4.97×10 -7 m 2 / s.
[0118] Constant pressure specific heat C P The constant pressure specific heat of the elastic layer was measured using a differential scanning calorimeter (product name: DSC823e, manufactured by Mettler Toledo K.K.). Specifically, aluminum pans were used as the sample pan and the reference pan. First, as a blank measurement, both pans were empty and kept at a constant temperature of 15°C for 10 minutes, then the temperature was raised to 215°C at a rate of 10°C / min, and the temperature was kept at a constant temperature of 215°C for another 10 minutes. Next, 10 mg of synthetic sapphire with a known low-pressure specific heat was used as a reference material, and measurements were performed using the same program. Next, a measurement sample of 10 mg, the same amount as the synthetic sapphire reference material, was cut out from the elastic layer, and set in the sample pan, and measurements were performed using the same program. These measurement results were analyzed using specific heat analysis software attached to the differential scanning calorimeter, and the constant pressure specific heat C at 25°C was calculated from the average value of five measurement results. P was calculated. As a result, the specific heat at constant pressure of the elastic layer was found to be 1.05 J / (g·K).
[0119] ·Density ρ The density of the elastic layer was measured using a dry automatic density meter (product name: Accupyc 1330-01, manufactured by Shimadzu Corporation). 3 A sample cell was used, and a sample piece was cut out from the elastic layer so as to fill approximately 80% of the cell volume. The mass of this sample piece was measured and then placed in the sample cell. This sample cell was set in the measurement section of the device, and helium was used as the measurement gas. After gas replacement, the volume measurement was carried out 10 times. The density of the elastic layer was calculated from the mass of the sample piece and the measured volume for each measurement, and the average value was calculated. As a result, the density of the elastic layer is 1.53 g / cm 3 It was.
[0120] From the above, the unit converted specific heat of the elastic layer at constant pressure C p (J / (kg K)) and density ρ(kg / m 3 ), and the measured thermal diffusivity α(m2 The thermal conductivity λnd of the elastic layer in the thickness direction was calculated for each longitudinal region from the thermal conductivity (λ / s). The results were 1.50 W / (m K) in the longitudinal center region and 0.80 W / (m K) in the end regions.
[0121] (3-2) Thermal conductivity of the elastic layer in the longitudinal direction The thermal conductivity λmd of the elastic layer in the longitudinal direction was calculated from the following formula. λmd=αmd×Cp×ρ In the formula, αmd is the thermal diffusivity in the longitudinal direction (m 2 / s), Cp is the specific heat at constant pressure (J / (kg K)), ρ is the density (kg / m 3 ). Here, the specific heat at constant pressure Cp and density ρ were determined by the above-mentioned method, and the thermal diffusivity αmd in the longitudinal direction and the thermal diffusivity αtd in the circumferential direction were determined by the following method.
[0122] The measurements were performed at room temperature (25°C) using a light AC thermal diffusivity measuring device (product name: LaserPIT, manufactured by Advance Riko). First, the elastic layer sample was cut into a 5 x 30 mm sample piece with a cutter knife so that the longitudinal or circumferential direction was 30 mm. Next, a black body paint (product name: JSC-3, manufactured by Japan Sensor Co., Ltd.) was applied to the surface of the sample piece, and the sample was baked for 20 minutes in an electric furnace set at 150°C to prepare a sample. Each sample was measured twice under the following conditions, and the average value was calculated. The measurement conditions were room temperature, in a vacuum, Total Time (total measurement time) 1500 sec, Sampling 2, Period (1 / frequency) 5, Rate (movement speed of the sample mounting table) 10 μm / s, and Level (movement distance of the sample mounting table) 3000 μm. Furthermore, the inventors have confirmed in advance that there is almost no variation between devices and that there is no problem in directly comparing the measured values from one device by examining samples cut from a bulk body that exhibits isotropic thermal conductivity. That is, the thermal conductivity measured with the cyclic heating method thermal property measuring device (product name: FTC-1, manufactured by Advance Riko Co., Ltd.) and the thermal conductivity measured with the optical AC method thermal diffusivity measuring device (product name: LaserPIT, manufactured by Advance Riko Co., Ltd.) were almost equal.
[0123] The constant pressure specific heat Cp (J / (kg K)) and density ρ (kg / m 3 ), and the measured thermal diffusivity αmd(m 2 / s) and αtd(m 2 The thermal conductivity λmd of the elastic layer in the longitudinal direction was calculated for each region from the thermal conductivity (λmd / s). The results were 1.29 W / (m K) in the longitudinal center region and λmd = 2.01 W / (m K) in the end regions.
[0124] (3-3) Average degree of alignment f L , average alignment angle Φs To determine the degree of alignment of the large particle size filler in each region of the elastic layer in the longitudinal direction and the alignment angle of the small particle size filler, 10 samples each measuring 5 mm in length, 5 mm in width, and the full thickness of the fixing belt were taken from each region of the manufactured fixing belt, and five first cross sections in the thickness-circumferential direction and five second cross sections in the thickness-longitudinal direction were polished using an ion beam. The first cross section of the elastic layer and the second cross section of the elastic layer were observed with a laser microscope, and cross-sectional images of an area of 150 μm × 100 μm were obtained (Figure 8(a)). The obtained cross-sectional images were binarized using Otsu's method, and a first binarized image was obtained from the first cross section, and a second binarized image was obtained from the second cross section (Figure 8(b)). The circle equivalent diameter of each filler in the obtained first and second binarized images was calculated, and the images were divided into an image in which only large particle size fillers 7 with a circle equivalent diameter of 5 μm or more remained (Figure 8(c)), and an image in which only small particle size fillers 8 with a circle equivalent diameter of less than 5 μm remained (Figure 8(d)). Two-dimensional Fourier transform analysis was performed on the large particle size filler image and the small particle size filler image to obtain elliptical plot diagrams showing the direction and degree of filler arrangement (Figures 8(e) and 8(f)). The large particle size arrangement degree and small particle size arrangement angle were obtained from the obtained elliptical plot diagrams, and the average arrangement degree f of large particle size fillers of 10 samples for each region was calculated. L and the average arrangement angle Φ of the small particle size filler s asked for.
[0125] (4) Actual machine evaluation (fixing ability, image quality, durability) <Adhesion evaluation> The fixing belt thus obtained was incorporated into a thermal fixing device of an electrophotographic copying machine (product name: imagePRESS C850, manufactured by Canon Inc.). This thermal fixing device was then installed in the copying machine. Using this copying machine, the fixing temperature was set lower than the standard fixing temperature, and a fixing belt having a basis weight of 300 g / m was fixed. 2 Cardboard (Product name: UPM Finesse gloss 300g / m 2 A solid cyan image was formed on a photosensitive drum (manufactured by UPM Co., Ltd.).
[0126] Specifically, the fixing temperature of the thermal fixing device was adjusted from 195° C., which is the standard fixing temperature in the copier, to 175° C., and five solid cyan images were formed in succession, and the image density of the fifth solid image was measured. Next, the toner surface of the solid image was heated to 4.9 kPa (50 g / cm 2 The toner surface was rubbed three times in the same direction with Silbon paper under a load of 1000 g, and the image density after rubbing was measured. If the decrease in image density before and after rubbing (= [image density difference before and after rubbing / image density before rubbing] x 100) was less than 5%, it was determined that the toner had been fixed to the cardboard. The results were evaluated according to the following criteria. A reflection densitometer (manufactured by Macbeth) was used to measure the image density. Rank A: The toner was fixed to the thick paper at a fixing temperature of 175°C. Rank B: The toner was fixed on the thick paper at a fixing temperature of 180°C. Rank C: The toner was fixed on the thick paper at a fixing temperature of 185°C. Rank D: The toner was not fixed to the thick paper at a fixing temperature of 185°C.
[0127] <Evaluation of temperature rise in non-paper passing areas> The evaluation of the temperature rise in the non-paper passing area was performed based on the surface temperature of the non-paper passing area of the fixing belt 3 measured after continuously printing A4 size paper (product name "CS-680", manufactured by Canon Inc.) at 90 sheets / min for 10 minutes in an environment of low temperature (about 15°C) and low humidity (about 10%). Specifically, 300 sheets were continuously printed while adjusting the heating temperature by the induction heating member 13 so that the surface temperature of the fixing belt 3 located 90° upstream from the fixing nip portion N in the conveying direction of the recording medium was maintained at 195°C. After the 300 sheets were continuously printed, the surface temperature of the non-paper passing area of the fixing member 11 (area where A4 landscape size paper does not pass) was measured with a radiation type thermometer, and the temperature change from the initial temperature (first sheet of paper passed) was evaluated based on the following criteria. Rank A: The temperature rise from the initial temperature in the non-paper passing area (first sheet of paper passing) is 30°C or less. Rank B: The temperature rise from the initial temperature in the non-paper passing area (first sheet of paper passing) is more than 30°C and less than 40°C Rank C: The temperature rise from the initial temperature in the non-paper passing area (first sheet of paper passing) is more than 40°C and less than 50°C Rank D: The temperature rise from the initial temperature in the non-paper passing area (first paper passing) is greater than 50°C.
[0128] <Durability evaluation> With the fixing temperature set to the standard fixing temperature (195°C), cyan solid images were continuously formed on A4-sized plain paper, and the number of sheets at which the elastic layer of the fixing belt was broken or plastically deformed was recorded and evaluated according to the following criteria. If the elastic layer of the fixing belt was still not broken or plastically deformed even after the number of images reached 740,000 sheets, image formation was stopped at 740,000 sheets. Rank A: No breakage or plastic deformation was observed in the elastic layer of the fixing belt even after 740,000 images were formed. Rank B: No destruction or plastic deformation occurred in the elastic layer of the fixing belt even after 600,000 images were formed, but destruction or plastic deformation occurred in the elastic layer of the fixing belt after 740,000 images were formed. Rank C: The elastic layer of the fixing belt was not broken or plastically deformed even after 100,000 images were formed, but was broken or plastically deformed after 600,000 images were formed. Rank D: Destruction or plastic deformation occurred in the elastic layer of the fixing belt after image formation on 100,000 sheets.
[0129] [Example 2] A fixing belt was produced and evaluated in the same manner as in Example 1, except that the volume ratio of the metallic silicon filler was 38 vol %.
[0130] [Example 3] A fixing belt was produced and evaluated in the same manner as in Example 1, except that the filler was 44 vol% large particle size alumina (product name: AO-509, manufactured by Admatec Co., Ltd., average particle size 10 μm) and 3 vol% small particle size alumina (product name: AO-502, manufactured by Admatec Co., Ltd., average particle size 0.7 μm), making the total filler amount 47 vol%.
[0131] [Example 4] A fixing belt was produced and evaluated in the same manner as in Example 1, except that the electric field was applied while the corona charger was reciprocally vibrated at 3 Hz and ±5 mm in the longitudinal direction by a reciprocating mechanism during application of the electric field. As a result, intermediate regions with a width of 5 mm were formed on both sides of the longitudinal central region of Example 1.
[0132] [Example 5] A fixing belt was produced and evaluated in the same manner as in Example 3, except that the electric field was applied while the corona charger was reciprocally vibrated at 3 Hz and ±5 mm in the longitudinal direction by a reciprocating mechanism during application of the electric field. As a result, intermediate regions with a width of 5 mm were formed on both sides of the longitudinal central region of Example 3.
[0133] [Comparative Example 1] A fixing belt was produced and evaluated in the same manner as in Example 3, except that no electric field was applied.
[0134] [Comparative Example 2] The filler was 50 vol% of large particle alumina (product name: AO-509, manufactured by Admatec Co., Ltd., average particle size 10 μm) and 3 vol% of small particle alumina (product name: AO-502, manufactured by Admatec Co., Ltd., average particle size 0.7 μm), making the total filler amount 53 vol%, and no electric field was applied. A fixing belt was produced and evaluated in the same manner as in Example 1 except for the above.
[0135] [Comparative Example 3] The volume ratio of the metallic silicon in the filler was set to 38 vol %, and no electric field was applied. A fixing belt was produced and evaluated in the same manner as in Example 1 except for the above.
[0136] [Comparative Example 4] The volume ratio of the metal silicon in the filler was set to 38 vol %, and an electric field was applied over the entire longitudinal area. A fixing belt was produced and evaluated in the same manner as in Example 1 except for the above.
[0137] [Comparative Example 5] The volume ratio of the metal silicon in the filler was set to 49 vol %, and no electric field was applied. A fixing belt was produced and evaluated in the same manner as in Example 1 except for the above.
[0138] The results are shown in Table 1 (Examples) and Table 2 (Comparative Examples).
[0139] [Table 1]
[0140] [Table 2]
[0141] In all the examples, λnd / λmd was 1.1 or more in the longitudinal center region 0.12L or more from both ends of the elastic layer, and λnd / λmd was 0.9 or less in the end region including 0.05L or less from both ends of the elastic layer. And, in all the examples, good results were obtained, with A rank or B rank, in fixation, temperature rise in non-paper passing region, and durability. In particular, in the examples 4 and 5 in which the intermediate region 4b is provided in the elastic layer by the charger reciprocating mechanism, durability was extremely good, and all durability was ranked A. This is thought to be because the load on the rubber caused by the shear force in the conveying direction generated by paper conveyance at the boundary between the paper passing region and the non-paper passing region was reduced by forming the intermediate region. And, in the examples 1, 2, and 4, λnd in the longitudinal center region is 1.3W / (m·K) or more, and λmd in the end region is 1.3W / (m·K) or more. These showed better performance in the evaluation of fixability and temperature rise in non-paper passing areas compared to Example 3, where λnd in the longitudinal central region was less than 1.3 W / (m·K) and λmd in the edge regions was less than 1.3 W / (m·K). It is clear that λnd and λmd of 1.3 W / (m·K) or more are preferable because Comparative Example 2 showed good results in the evaluation of temperature rise in non-paper passing areas when λnd was 1.30 and λmd was 1.35 W / (m·K).
[0142] On the other hand, in the comparative example, since the thermal anisotropy of the thermal conductivity for each longitudinal region was not controlled, the results were ranked C or D in one of the items.
[0143] Although the above examples and comparative examples have been described with respect to fixing belts, it is easily understood that the same tendency is observed in the case of fixing rollers. [Industrial Applicability]
[0144] As described above, the present disclosure can be used for a fixing member for a thermal fixing device that has high thermal conductivity in the thickness direction in the paper passing area, high durability against repeated compression, etc., and is effective in suppressing excessive temperature rise in the non-paper passing area, and for a thermal fixing device. In addition, the thermal fixing device can stably fix (fix) a toner image transferred to a recording medium to the recording medium in an electrophotographic image forming apparatus equipped with the thermal fixing device, and can provide an electrophotographic image forming apparatus that does not require the installation of an end cooling fan or downtime. [Explanation of symbols]
[0145] 3 Base 4 Elastic layer 4a End area 4b Intermediate area 4c Longitudinal central area 401-1 1st section 401-2 2nd cross section 7 Large particle size filler 8. Small particle size filler 100 Fixing member 11 Fixing belt 12 Pressure Belt 13 Induction heating components 18 Heating roller 20 Pressure roller 31 Ceramic heater 33 Pressure roller
Claims
1. A fixing member for a thermal fixing device having a substrate and an elastic layer on the substrate, comprising: the elastic layer includes a silicone rubber and a filler dispersed in the silicone rubber, When the thermal conductivity of the elastic layer in the thickness direction is λnd, the thermal conductivity in the longitudinal direction is λmd, and the total length of the elastic layer in the longitudinal direction is L, A central region of the elastic layer extending from each end of the elastic layer in the longitudinal direction to a center of the elastic layer in the longitudinal direction of the elastic layer is 0.12×L or more in terms of λnd / λmd of 1.1 or more; and The fixing member is characterized in that the elastic layer has end regions in which λnd / λmd is 0.9 or less between each end of the elastic layer in the longitudinal direction and 0.12×L toward the center of the elastic layer in the longitudinal direction.
2. 2. The fuser member of claim 1, wherein the λnd of the central region is 1.3 W / (m·K) or more and the λmd of the edge regions is 1.3 W / (m·K) or more.
3. A first binarized image having a size of 150 μm×100 μm is obtained at any five points on a first cross section in a thickness-circumferential direction in the central region, and a second binarized image having a size of 150 μm×100 μm is obtained at any five points on a second cross section in a thickness-longitudinal direction; The average alignment degree f of large particle size filler particles having a circle equivalent diameter of 5 μm or more in each of the binarized images L is equal to or greater than 0.00 and equal to or less than 0.15, The average arrangement angle Φ of small particle size filler particles having a circle equivalent diameter of less than 5 μm in each of the binarized images S The fixing member according to claim 1 or 2, wherein the angle is 60° or more and 120° or less.
4. A first binarized image having a size of 150 μm×100 μm is obtained at any five points of a first cross section in a thickness-circumferential direction in the end region, and a second binarized image having a size of 150 μm×100 μm is obtained at any five points of a second cross section in a thickness-longitudinal direction; The average alignment degree f of large particle size filler particles having a circle equivalent diameter of 5 μm or more in each of the binarized images L is equal to or greater than 0.00 and equal to or less than 0.15, The average arrangement angle Φ of small particle size filler particles having a circle equivalent diameter of less than 5 μm in each of the binarized images S The fixing member according to any one of claims 1 to 3, wherein the angle is 30° or less or 150° or more.
5. The fixing member according to any one of claims 1 to 4, wherein the elastic layer has an intermediate region between the central region and the end regions, where λnd / λmd is greater than 0.9 and less than 1.
1.
6. A first binarized image having a size of 150 μm×100 μm is obtained at any five points on a first cross section in a thickness-circumferential direction in the intermediate region of the elastic layer, and a second binarized image having a size of 150 μm×100 μm is obtained at any five points on a second cross section in a thickness-longitudinal direction; The average alignment degree f of large particle size filler particles having a circle equivalent diameter of 5 μm or more in each of the binarized images L is equal to or greater than 0.00 and equal to or less than 0.15, The average arrangement angle Φ of small particle size filler particles having a circle equivalent diameter of less than 5 μm in each of the binarized images S The fuser member of claim 5 , wherein the angle is greater than 30° and less than 60°, or greater than 120° and less than 150°.
7. 7. The fixing member according to claim 1, wherein the fixing member is an endless fixing belt.
8. The fixing member according to claim 7 , further comprising a surface layer on an outer periphery of the elastic layer.
9. The fuser member of any one of claims 1 to 8, wherein the substrate comprises at least one selected from the group consisting of nickel, copper, iron, and aluminum.
10. A thermal fixing device having a fixing member for heating and a pressure member arranged opposite the fixing member, the fixing member being the fixing member according to any one of claims 1 to 9.
11. 11. The thermal fixing device according to claim 10, further comprising a heating means for heating a substrate of the fixing member.
12. 12. The thermal fixing device according to claim 11, wherein the heating means is an induction heating means, and the substrate of the fixing member is a substrate that can be heated by induction heating.
13. 12. The thermal fixing device according to claim 11, wherein the heating means is a heater for heating the substrate.
14. 14. The thermal fixing device according to claim 13, wherein the heater is disposed in contact with an inner circumferential surface of the fixing member.
Citation Information
Patent Citations
Heat fixing member and heat fixing apparatus
JP2006259712A
Fixing device and image forming apparatus having the same
JP2009175381A
Fixing device
JP2017009786A
Fixing member and heat fixing device
JP2019211701A
Fixing member and thermal fixing device
JP2019215531A